SPIRITUAL VALUE-BASED EDUCATIONAL MANAGEMENT IN SHAPING SCHOOL CULTURE: A CASE STUDY AT SMA PLUS HAMZANWADI II NAHDLATUL WATHAN - Lalu Abdul Muhyi Abidin; Nurmiati (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
Spiritual values are increasingly recognized as foundational elements in contemporary educational management. However, the integration of spiritual values into the managerial functions of Islamic boarding school-based secondary schools in Indonesia remains underexplored. This study examines the implementation of spiritual values-based educational management across the planning, organizing, executing, and supervising functions at SMA Plus Hamzanwadi II Nahdlatul Wathan, and its influence on school culture. Utilizing a qualitative single-case study design, data were collected through in-depth interviews, participatory observation, and document analysis with purposively selected principals, teachers, and students. Data analysis followed an interactive model, with validity ensured through source and technique triangulation. The findings demonstrate that embedding honesty, discipline, and responsibility within the school's management cycle fosters a religious, disciplined, and harmonious school culture. Principal leadership and exemplary conduct are identified as primary supporting factors, while inconsistent implementation and external influences present significant challenges. This study proposes a conceptual model linking values-based spiritual management to the development of school culture in Islamic boarding school-based secondary education in Indonesia, and provides practical implications for formulating values-based managerial policies